2016
DOI: 10.1212/wnl.0000000000002375
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric pathology in primary progressive aphasia with progranulin mutations and TDP inclusions

Abstract: Distribution of TDP-43 inclusions and neurons, and to a smaller extent of activated microglia, show a regional and hemispheric pattern consistent with disease phenotype and known patterns of atrophy in PPA with GRN mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 36 publications
5
42
0
Order By: Relevance
“…23,24 Lateralization of postmortem disease has been shown in rare prior postmortem studies, either qualitatively 3 or quantitatively in a small sample of FTLD-TDP. 3,14 Moreover, our digital approach enabled us to detect novel evidence of regional and individual-patient variability (see Fig 2). In our rare bilateral dataset, we found overall left lateralization of cortical pathology in FTLD-TDP and FTLD-Tau, consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 Lateralization of postmortem disease has been shown in rare prior postmortem studies, either qualitatively 3 or quantitatively in a small sample of FTLD-TDP. 3,14 Moreover, our digital approach enabled us to detect novel evidence of regional and individual-patient variability (see Fig 2). In our rare bilateral dataset, we found overall left lateralization of cortical pathology in FTLD-TDP and FTLD-Tau, consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has studied hemispheric and regional brain involvement in PPA variants using in vivo techniques of neuroimaging, 8,9 but postmortem studies characterizing regional pathology are very rare, and antemortem imaging is seldom cross-validated with postmortem pathologic burden. 12 Postmortem lateralization of pathology has been measured in limited PPA cases with FTLD-TDP, [13][14][15][16] whereas distribution of pathology in PPA with FTLD-Tau is understudied. 12 Postmortem lateralization of pathology has been measured in limited PPA cases with FTLD-TDP, [13][14][15][16] whereas distribution of pathology in PPA with FTLD-Tau is understudied.…”
mentioning
confidence: 99%
“…Another study investigated the opposite effect, by inducing chronic inflammation in a transgenic mouse model expressing a genomic fragment of the human TDP‐43 gene, and demonstrated enhanced cytoplasmic mislocalization and aggregation of TDP‐43 . In PPA‐TDP cases with GRN mutations, we found high densities of activated microglia, but failed to detect a strong correlation between burden of pathological inclusions and microglial densities . Similar to our findings in PPA‐TDP cases with GRN mutations, the present study of PPA‐TDP cases without known mutations revealed only a modest correlation between densities of microglia and mature TDP‐43 inclusions.…”
Section: Discussionmentioning
confidence: 98%
“…Lack of a consistent relationship between TDP‐43 inclusion and activated microglia densities in our study suggests that the relationship may not be direct. Our findings do support the notion that an upregulation of activated microglia in neurodegenerative diseases occurs in close proximity to pathological inclusions . In the context of FTLD‐TDP, a number of studies have shown a direct effect of pathological proteins on microglial activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation